Penile melanoma: a pathological report of two cases - Boglárka Pósfai; Márton Szentkereszty; Fanni Sánta; Zoltán Bajory; Andrea Simon; Zsófia Kozéki; Ildikó Csányi; Mahmut Akgul; Levente Kuthi (BMC, 2023)
Abstract Background Penile melanoma (PM) is a rare tumor, accounting for less than 2% of all penile cancers. PM can occur on the surface of the glans, foreskin, and opening of the urethra. Furthermore, PM primarily affects older individuals and is not associated with sun exposure. Currently, there is no specific staging system for genitourinary tract melanomas, so these tumors are typically staged using the criteria for cutaneous melanoma. Limited data in the literature suggests that PM generally has a poor clinical prognosis. Case presentation Here, we describe two cases of PM. The first case affected a 62-year-old male who presented with hematuria and a painful tumor in the distal urethra, leading to a suspicion of penile cancer. The second case involved a 68-year-old male who noticed a rapidly evolving dark spot on his foreskin. Histological analysis confirmed the presence of melanoma in both patients. The tumors showed a diffuse and strong PRAME-positivity and lacked BRAF mutation in both cases. Additionally, the second tumor harbored an activating CKIT mutation. An enhanced PD-L1 expression was observed in both tumors. Conclusions We presented two rare forms of mucosal melanoma and highlighted the entities in the differential diagnosis. Based on our experience PRAME is a helpful marker for making the diagnosis of PM, and PD-L1 can predict the success of the immunotherapy. We also emphasize the need for an organ-specific staging system for PMs.